The Effect of Scrapbook Media on Students’ Skills Speaking /Pengaruh Media Scrapbook terhadap Keterampilan Berbicara Siswa - Maryam Faizah; Ahmad Nur Ghofir Mahbudin; Imam Rofiki (Al-Mudarris: Journal Of Education, 2020)
Speaking skills are the ability of someone to say articulation sounds or words that have meaning to convey ideas, thoughts and ideas. The research objectives are (1) knowing student responses to Scrapbook media in thematic learning; (2) find the effect of Scrapbook media on student speaking skills. The research approach is quantitative with experimental type. The design of this study is non-equivalent control group design with population of all students grade V MI Nasyrul Ulum Bocek Malang and the number of students in the sample of each class (control and experiment class) is 30. The research instrument used questionnaire and observation sheet. The data obtained were analyzed by Independent Sample t-test. From the results responses showed there were 76% good and correct speaking skills. From the t-test results of speaking skills with the Equeval variance not assumed is 3.980 with a probability of 0.00 and the probability value 0.00 <0.05 then H0 is rejected and H1 is accepted. Based on the results of the calculation, there is a significant increase in the experimental class from pre-test value 26.66% increased to 76.66% in the post-test value. For the control class, pre-test value 20% becomes 30% in the post-test value. In conclusion, Scrapbook media has a significant effect on student speaking skills.